Analysis of Work Shifts and Mental Workload with Work Fatigue in Water Treatment Plant Operators at Perumdam Muara Tirta Gorontalo City Using NASA-TLX and SOFI Methods - Utiarahman, Ramadhan; Jusuf, Herlina; Maksum, Tri Septian (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Work fatigue is a condition of workers who are weakened to do a job and have an impact on decreasing work productivity. Factors that trigger work fatigue include internal factors (age, gender, work position) and external factors (workload, length of work, work period, work shift and work environment). The purpose of this research was to analyze work shifts and mental workload with work fatigue in Water Treatment Plant operators at Perumdam Muara Tirta Gorontalo City using the NASA-TLX and SOFI methods. The type of research used was analytic observational with a cross-sectional research design. The research instrument used the NASA-TLX and SOFI questionnaires. Data were analyzed using the Spearman’s Rank correlation test. The results of the study of work shifts of Water Treatment Plant operators using the fast rotation shift system. Mental workload was mostly in the moderate category with 20 operators (51.3%) and work fatigue was mostly in the moderate category with 26 operators (66.7%). There is a strong relationship between work shifts and work fatigue (?-value = 0.000; r = 0.653) and there is a quite strong relationship between mental workload and work fatigue (?-value = 0.008; r = 0.417). It is recommended that operators be able to adjust their working hours properly to the demands of duties and responsibilities outside of work.